Brittle failure of inclined key‐hole notches in isostatic graphite under in‐plane mixed mode loading. Issue 9 (16th April 2013) - Lazzarin, P.; Berto, F.; Ayatollahi, M. R.; Susmel, L.; Iacoviello, F.; Ferro, G.
ABSTRACT In the present contribution, the fracture behaviour of specimens made of isostatic graphite and weakened by inclined key‐hole notches is investigated. Different loading mixities are considered varying the inclination angle of the notch with respect to the direction of the applied load. The new data permit to enlarge the scarce number of results available in the literature for the same material under prevalent in‐plane shear loading. A criterion based on local energy is used for the fracture assessment to summarise all the data in a single scatter band independent of the notch geometry and mode mixity. The local energy‐based criterion allows to predict with sound accuracy the critical loads of the specimens independent of the mode mixity from pure mode I to prevalent mode II. A final synthesis is reported in the paper, summarising the new data together with previous results on the same material from U‐notched specimens subjected to mode I + II loading.